Acalypha fruticosa L. leaf extract mediated synthesis of ZnO nanoparticles: Characterization and antimicrobial activities. (2020) - Vijayakumar, S.; Arulmozhi, P.; Kumar, N.; Sakthivel, B.; Prathip Kumar, S.; Praseetha, P.K.
Abstract: Today, green synthesized nanoparticles have derived attention due to their unique properties such as low cost and eco-friendly nature. We, for the first time green synthesized ZnO nanoparticles using Acalypha fruticosa leaf extracts and were characterized by UV–Visible spectroscopy, X-ray Diffraction, Fourier Transfer Infrared Spectroscopy, High Resolution Scanning Electron Microscopy, Energy Dispersive Analysis of X-ray, Atomic Force Microscopy, and Transmission Electron Microscopy. Further the bio-synthesized nanoparticles were tested against pathogenic microorganisms using agar well diffusion method. In addition, Minimum inhibitory concentration (MIC), Minimum bactericidal and fungicidal concentration (MBC /MFC) were also studied. Thus, this present study concluded that ZnO nanoparticles exhibited potential antimicrobial activity when compared with plant extracts and standard drug.